2019
DOI: 10.1108/ijhcqa-06-2018-0138
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles’ influence on the quality of nursing care

Abstract: Purpose The purpose of this paper is to investigate managers’ leadership styles, from the perspective of registered nurses, and its effects on the quality of nursing care in both the private and public healthcare sectors. An additional aim is to assess the relationship between leadership styles and particular organisational outcomes. Design/methodology/approach The sample for this quantitative research study was comprised of 400 respondents, among which 50 were nurse managers, 150 were staff nurses and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 29 publications
2
53
2
4
Order By: Relevance
“…Other factors influencing satisfaction with current position that require special attention of nurse managers are direct‐care nurse staffing levels, absenteeism and work experience. Nurse managers, their leadership style and the work environment they manage play key roles in the quality of the nursing care provided in their units and staff outcomes (Alloubani et al, 2019; Pishgooie, Atashzadeh‐Shoorideh, Falcó‐Pgueroles, & Ltfi, 2019; Saleh et al, 2018). The findings highlight the importance of acknowledging satisfaction with nursing position as a complex phenomenon, requiring the full attention of nurse managers, continuing attention and further research of nurse scholars, and awareness of nurse clinicians and other nursing staff of what factors contribute to their well‐being and satisfaction at work.…”
Section: Implications For Practicementioning
confidence: 99%
“…Other factors influencing satisfaction with current position that require special attention of nurse managers are direct‐care nurse staffing levels, absenteeism and work experience. Nurse managers, their leadership style and the work environment they manage play key roles in the quality of the nursing care provided in their units and staff outcomes (Alloubani et al, 2019; Pishgooie, Atashzadeh‐Shoorideh, Falcó‐Pgueroles, & Ltfi, 2019; Saleh et al, 2018). The findings highlight the importance of acknowledging satisfaction with nursing position as a complex phenomenon, requiring the full attention of nurse managers, continuing attention and further research of nurse scholars, and awareness of nurse clinicians and other nursing staff of what factors contribute to their well‐being and satisfaction at work.…”
Section: Implications For Practicementioning
confidence: 99%
“…Nursing management influences care outcomes (Aiken et al, 2016; Wong, Cummings, & Ducharme, 2013), but we found only a few studies concerning directly psychiatric nursing managers. Alloubani, Akhu‐Zaheaya, Abdelhafiz, and Almatari (2019) examined psychiatric nursing managers' leadership styles, but Blegen and Severinsson (2011) addressed mental health nursing management and leadership more broadly. Because management is a key component of strategies that aim to reduce containment methods, it is important to identify nursing managers' attitudes towards containment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most of the available research covers how a nurse manager's leadership style and work behavior in uence nursing outcomes. Multiple studies have identi ed a positive link between the relational leadership style and nurses' job satisfaction (3,6,40), while other research has linked this leadership approach with patient satisfaction (2,3,41). In addition, it is challenging for nurse managers to lead quality improvement in the complex everday environment of a health care organization (42).…”
Section: Introductionmentioning
confidence: 99%